2004
DOI: 10.1021/ma0491199
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Thermoplastic Elastomers

Abstract: Investigations of high molecular weight recombinant protein triblock copolymers demonstrate unique opportunities to systematically modify material microstructure on both nano-and mesolength scales in a manner not been previously demonstrated for protein polymer systems. Significantly, through the biosynthesis of BAB-type copolymers containing flanking, plastic-like end blocks and an elastomeric midblock, virtually cross-linked protein-based materials were generated that exhibit tunable properties in a manner c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 20 publications
2
146
0
3
Order By: Relevance
“…Wright et al and Nagapudi et al have reported systematic rheological studies of genetically synthesized self-assembling elastin-mimetic triblock polypeptides [153,154,201,202]. The copolymers composed of a plastic domain (its consensus repetitive sequence: VPAVG) as the end blocks and an elastomeric domain (its consensus repetitive sequence: VPGVG) as the middle block.…”
Section: Elastin-mimetic Polypeptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wright et al and Nagapudi et al have reported systematic rheological studies of genetically synthesized self-assembling elastin-mimetic triblock polypeptides [153,154,201,202]. The copolymers composed of a plastic domain (its consensus repetitive sequence: VPAVG) as the end blocks and an elastomeric domain (its consensus repetitive sequence: VPGVG) as the middle block.…”
Section: Elastin-mimetic Polypeptidesmentioning
confidence: 99%
“…Rheological measurements of an aqueous triblock copolymer solution as a function of temperature showed that the copolymers would be well-suited for biomedical applications. The loss modulus (G″) is higher than the storage modulus (G′) below the LCST, and G′ is higher than G″ above the LCST, indicating that above the LCST the solution converts from liquid-like to solid-like viscoelastic behavior [70,153,201,202]. They found that changing the length or hydrophilicity of the middle largely affected the viscoelastic and mechanical behavior of the copolymers when the same plastic domain was used [202].…”
Section: Elastin-mimetic Polypeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-known fibrous proteins are silk, collagen, elastin, mussel adhesive proteins, keratin, wheat glutenin and resilin (Kiick, 2007). By combining repeat sequences of the various natural fibrous proteins or even completely synthetic sequences, and changing the linker elements between the repeat sequences, a tremendous combinatorial range is available (Holland et al, 2007;Nagapudi et al, 2005). Obviously, this could also include sequences optimized for production in plants.…”
Section: Fibrous Proteinsmentioning
confidence: 99%
“…Recently, we have reported the synthesis of high molecular weight recombinant protein block copolymers using an approach, which affords significant flexibility in the selection and assembly of blocks of diverse size and structure. [7][8][9][10][11] This has led to the synthesis of a new class of BAB protein triblock copolymer composed of large polypeptide block sequences ranging from 400 to 1200 amino acids in length. This class of protein block copolymers are derived from elastin-mimetic polypeptide sequences in which identical endblocks of a hydrophobic, plastic-like sequence are separated by a central hydrophilic, elastomeric block.…”
Section: Introductionmentioning
confidence: 99%